ANALISIS PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, KEBIJAKAN DIVIDEN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN (Studi Di Bursa Efek Indonesia) - Arif Afendi (FE Program Studi Manajemen, 2018)
The purpose of this research is to analyze the influence of managerial ownership,dividend policy, profitability and size of corporate on capital structure. This research is usingpurposive sampling method for taking samples based on the defined criteria. The sample are50 manufacturing company listed in Indonesian Stock Exchange (IDX) during 2012 to 2016resulting 250 observations. The data was analysis by using multiple linear regressionsanalysis. The result of the research shows that managerial ownership has positive andsignificant influence to capital structure, dividend policy has negative but not significantinfluence to capital structure, profitability has positive and significant influence to capitalstructure and size of corporate has positive and significant influence to capital structure.Keywords: managerial ownership, dividend policy, profitability, size and capital structure